Multilingual Experimental Literature and Transnational Feminist Solidarities: Erín Moure and Kathy Acker - Melissa Tanti (Studies in 20th & 21st Century Literature, 2023)
The impulse toward multilingual writing has arisen as a prominent trend in contemporary women’s writing. Criticism and notions of the literary have to respond to, among other things, the fact that "we live in a world where a significant portion of the population is at least partially bi or multilingual" (Camboni 34). To be responsive to the "increasing multilingualism of writers necessitates new strategies for reading the polyvocality of texts" (Eagleton and Friedman 3). This paper considers the ways multilingual writing creates, “small scale modes of listening” (Maguire xix) that tune the reader to languages, identities, and cultures under erasure. Erín Moure’s multilingual repertoire includes writing in French, Galician, Spanish, Portuguese, Portunhol, and Romanian with fragments of Polish, Ukrainian, Yiddish, Hebrew, Russian, and Latin marking the Ukrainian setting in which the Elisa Sampedrín stories take place, as well as quotes in German, some Kanji and Greek. Kathy Acker employs a sophisticated multilingual register in her late corpus work that includes French, Spanish, German, and Farsi. This paper explores the ways multilingual writing creates the conditions for subaltern audibility, thereby setting the grounds for transnational feminist solidarities.
Keywords: Kathy Acker; Erin Moure; global feminism; multilingual writing; women' s literature; translation; transnational feminism; literary criticism